1990
DOI: 10.1016/0014-5793(90)81206-4
|View full text |Cite
|
Sign up to set email alerts
|

1H nuclear magnetic resonance study of the solution conformation of an antibacterial protein, sapecin

Abstract: The solution conformation of an antibacterial protein sapecin has been detennined by 'H nuclear magnetic resonance (NMR) and dynamical simulated annealing calculations. It has been shown that the polypeptide fold consists of one flexible loop (residues 4-12), one helix (residues 1523), and two extended strands (residues 2431 and 3W). It was found that the tertiary structure of sapecin is completely different from that of rabbit neutrophil defensin NP-5, which is homologous to sapecin in the amino acid sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 19 publications
0
75
0
Order By: Relevance
“…The recent NMR studies of Phormia defensin A in water have provided an insight into the three-dimensional arrangement of this molecule [XI, which is relevant to this Discussion (for an NMR analysis in methanol of the Sarcophaga peptide, see [7]). As shown in Fig.4B , Phormia defensin is characterized by the presence of three regions; an N-terminal loop (residues 1 -13; numbering is for Phormiu defensin); an a hclix (residua 14 -24) and an antiparallel p sheet (residues 25-40) with a turn involving residues 32-34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent NMR studies of Phormia defensin A in water have provided an insight into the three-dimensional arrangement of this molecule [XI, which is relevant to this Discussion (for an NMR analysis in methanol of the Sarcophaga peptide, see [7]). As shown in Fig.4B , Phormia defensin is characterized by the presence of three regions; an N-terminal loop (residues 1 -13; numbering is for Phormiu defensin); an a hclix (residua 14 -24) and an antiparallel p sheet (residues 25-40) with a turn involving residues 32-34.…”
Section: Discussionmentioning
confidence: 99%
“…Four groups of inducible antibacterial peptides or polypeptides have been isolated and totally or partially characterized, which are: the cecropins, 4-kDa cationic pcptides devoid of cysteines, which form two amphipathic tl helices ( [3], reviewed in [4]); the insect defensins, 4-kDa cationic peptides which contain six cysteine residues engaged in three intramolecular disulfide bridges and characterized by an amphipathic CI helix linked via two disulfide bridges to an antiparallel j? sheet [5][6][7][8]; three as yet incompletely characterized, small (2 -4-kDa) cationic proline-rich peptides or peptide families which are the apidaecins 191, abaecin [lo] and the drosocins (Bulet P. and Dimarcq J. L., unpublished results); several distinct polypeptides ranging in size over 8 -27 kDa, mostly cationic and frcquently rich in Correspondence to J. A. Hoffmann, Laboratoirc de Biologie Generalc, UniversitC Louis Pasteur, URA CNRS 1490, Bases xnoleculaires de la rtponsc immunitaire des insectes, 12 rue de l'universite, F-67000 Strasbourg, France…”
mentioning
confidence: 99%
“…The refolded native sapecin was re-purified by the reverse phase HPLC to remove the incorrectly folded products. The proper folding of sapecin was confirmed by the anti-bacterial activity with S. aureus and the comparison of the 1 H chemical shifts between the recombinant sapecin and sapecin derived from flesh fly (9). Site-directed mutations were designed and introduced by PCR with the corresponding synthetic primers.…”
Section: Expression and Purification Of Sapecin-sapecin Was Expressed Inmentioning
confidence: 99%
“…Sapecin consists of 40 amino acid residues, including three disulfide bonds, which are essential for the antibacterial activity (8). The solution structure of sapecin was solved in methanol by NMR techniques (PDB code 1L4V) (9). The structure revealed that the peptide consists of an N-terminal loop (residues 4 -12), an ␣ helix (residues [15][16][17][18][19][20][21][22][23], and a two-stranded ␤ sheet (residues 24 -31 and 34 -40), with three disulfide bridges connecting these structural elements.…”
mentioning
confidence: 99%
“…Defensins are 4 kDa cationic peptides with a characteristic six cysteine/three disulfide bridge pattern and three domains, a flexible amino-terminal loop, a central a-helix and a carboxy-terminal anti-parallel b-sheet (Hanzawa et al, 1990;Bonmatin et al, 1992;Bulet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%